Kinetics Adsorption of Fe Metal using Cellulose Acetate from Palm Fronds (Borassus Flabellifer): Kinetika Adsorpsi Logam Fe menggunakan Selulosa Asetat dari Pelepah Lontar (Borassus Flabellifer) - Iin Novianty; Erma; Saleh, Asri; Gani, Rahmiani (Al-Kimia, 2024)
Lontar palm fronds (Borassus flabellifer), containing 5.27% cellulose, can be converted into cellulose acetate, which serves as an effective adsorbent for binding iron metal. The adsorption method optimizes the binding of the adsorbate to the adsorbent based on mass and contact time. This study aims to characterize the cellulose acetate derived from lontar palm fronds and evaluate its efficacy as an adsorbent for iron (Fe) metal. The production stages of cellulose acetate include cellulose isolation, synthesis of cellulose acetate, and testing of acetyl content, with a degree of substitution valued at 2.24. Fourier transform infrared (FTIR) spectroscopy and atomic absorption spectrophotometry (AAS) were employed to characterize the cellulose acetate. The optimal absorption capacity for Fe metal was achieved with an adsorbent mass of 0.06 g, resulting in an absorption efficiency of 66.39%. The optimal contact time was determined to be 90 minutes, with an absorption efficiency of 47.56%. The adsorption kinetics of cellulose acetate for iron (Fe) followed the Pseudo Second Order model, with R² = 0.9935 and k = 0.0096.